The combination of normal saline and lactated Ringer's solution for large intravascular volume infusion - (:unkn) unknown (My University, 2004)
Objective: The aim of this study was to evaluate the perioperative effects of large intravascular volume infusion of both normal saline (NS) and lactated Ringer's (LR) solution on electrolytes and acid base balance. Materials and Methods: In 20 patients, aged between 20-70 years, undergoing major spine surgery, ASA I-II NS and LR solutions were infused at the rate of 20 mL.kg -1.h-1 peroperatively and 2.5 mL.kg-1.h -1 postoperatively by switching between the two solutions every other liter. Mean arterial pressure, heart rate, oxygen saturation, end-tidal carbondioxide pressure, central venous pressure, esophageal temperature were recorded every 15 minutes and crystalloid infusion volumes, urinary output, blood loss, and blood transfusion volumes were recorded hourly peroperatively. Electrolytes (Na+,K+,Cl-) and arterial blood gases were measured preoperatively, every hour peroperatively and at the 1 st, 2nd, 4th, 6th, 8th, 12th, 16th, 20th and 24th hours postoperatively. Results: Arterial pH, HCO3 and base excess values decreased and serum Cl- values increased significantly peroperatively. Arterial CO2 pressure increased significantly at peroperative 6th h (p<0.05). Conclusion: The combination of NS and LR solutions causes not only hyperchloremic acidosis peroperatively but also a mixed acidosis postoperatively.
Keywords: Hyperchloremic acidosis; Lactated Ringer's solution; Normal saline